CHARACTERIZATION AND APPLICATION OF WDSSB5 MONOCLONAL ANTIBODY FOR THE DETECTION OF DENGUE VIRUS IN C6/36 CELL LINE USING IMMUNOCYTOCHEMICAL METHOD - Nurminha Nurminha; Sitti Rahma Umniyati; Wayan T Amarta (Pusat Kedokteran Tropis, 2012)
ABSTRACTIntroducition: Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHF) are caused by Dengue virus that consists of 4 serotypes of Dengue Virus (DENV) 1, 2, 3 and 4. Isolation of Dengue virus using C6/36 cell is considered as a gold standard for the diagnosis of Dengue virus infection. Dengue Team of Gadjah Mada University successfully produced monoclonal antibodies of DENV 3 originating from hybrid cells of DSSC7, DSSE10 and WDSSB5. The detection of Dengue virus’s antigens of Ae. aegypti in human blood smear with Streptavidine Biotin Peroxide Complex (SBPC) immunocytochemistry method using DSSC7 primary antibody is highly sensitive and specific, whereas using WDSSB5 monoclonal antibody yet to be characterized. Objective: The study aimed to identify characterization and application of WDSSB5 monoclonal antibody as primary antibody for detection of Dengue virus originating from serum of patients with Dengue infection which was inoculated in C6/36 cell line using SBPC immunocytochemistry method.Methods: The study was experimentally designed. Propagation of WDSSB5 hybridoma cell was performed in vitro and in vivo. The characterization consisted of classification of WDSSB5 monoclonal antibody, examination of WDSSB5 ascites protein level, sensitivity and specificity of immunocytochemical SBPC method using WDSSB5 primary antibody and specificity of monoclonal antibody against Dengue antigen with Dot Blot method. Dengue virus obtained from patients was inoculated in C6/36 cell. Detection of Dengue virus antigen was performed by SBPC immunocytochemistry method with WDSSB5 monoclonal antibody as primary antibody. Positive control was made using C6/36 cell infected with DENV 1, 2, 3, 4 and inoculated in C6/36 cell, whereas negative control uses cell C6/36 not infected with Dengue virus.Results: There was WDSSB5 monoclonal antibody detected in this research which was belonged to IgG class and IgG1 subclass. The least content of WDSSB5 monoclonal antibody that can detect Dengue antigen in C6/36 cell was 2.2 µg/µL. The WDSSB5 monoclonal antibody was sensitive to detect DENV 1, 2, 3, 4 antigens in C6/36 cell using SBPC immunocytochemistry method.Conclusion: There was WDSSB5 monoclonal antibody specific againts Dengue virus identified in this study. WDSSB5 monoclonal antibody belonged to class IgG and subclass IgG1. WDSSB5 Monoclonal antibody can be applied to detect Dengue virus originating from serum of patients positively carrying Dengue virus inoculated in C6/36 cell using SPBC immunocytochemistry method. Keywords: Dengue Virus, immunocytochemical, monoclonal antibody, C6/36 cell